(untitled) (Journal of Comparative Social Work, 2012)
Working in a rural community locates the professional in a wider social network as community members often expect more from their professionals; not only as service providers, but also as engaged members of the community. This can result in the rural social worker being highly visible both personally and professionally and it can also lead to overlapping relationships. These higher expectations can place stress on the worker in terms of maintaining accepted professional roles and a sense of professional identity. This qualitative study explores the first-hand experiences of a cross-section of service providers in more than a dozen communities within northwestern Ontario and northern Manitoba, Canada. The responses of the participants provide some insight into how rural practitioners maintain their professional identity when working within the unique demands of the rural and remote context. Recurring themes from the interviews suggest that these professionals craft their own informal decision-making processes to address intersecting roles, community gossip, and personal isolation, even while, in some cases, practicing in their home community. The findings provide greater understanding of the pressures and realities of working in small remote towns and the challenges of responding to the expectations and realities of relationships including the expectation of working with friends and family members of friends or colleagues: issues that have not been adequately studied in the literature to date.